THE EFFECTIVENESS OF ONLINE EDUCATION IN DEVELOPING WRITING SKILLS - Karimberganova Shahnoza Muxammad qizi,; Ruzmetova Diana Kamilovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This paper discusses how online education contributes to enhancing the writing skills of second language learners. With the rapid development of digital technologies, writing instruction has gradually moved from the traditional classroom-based  approach  to  virtual  learning  environments.  This  article  focuses  on  the advantages,  limitations,  theoretical  backgrounds,  technological  tools,  feedback mechanisms, and psychological factors that influence  the process of  online writing development.  The  findings  of  research  suggest  that  online  education  may  lead  to significant  improvement  in  the  writing  proficiency  of  learners  if  it  is  supported  by structured feedback, collaborative tasks, and digital literacy. However, its pace might be hampered by limitations including reduced teacher presence, loss of motivation, and some  technical  issues.  This  paper  concludes  that  online  education  works  very effectively when supported by sound instructional design.